Specification for harmonized system of quality assessment for electronic components. Fixed capacitors for use in electronic equipment. Blank detail specification: fixed metallized polyethylene terephthalate film dielectric d.c. capacitors. Assessment level E. (15th January 1984) - British Standards Institution,
No abstract available